Synaptic dysfunction in ALS and FTD: anatomical and molecular changes provide insights into mechanisms of disease - Gelon, Pauline A.; Dutchak, Paul A.; Sephton, Chantelle F. (Frontiers in Molecular Neuroscience, 2022)
Synaptic loss is a pathological feature of all neurodegenerative diseases including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). ALS is a disease of the cortical and spinal motor neurons resulting in fatal paralysis due to denervation of muscles. FTD is a form of dementia that primarily affects brain regions controlling cognition, language and behavior. Once classified as two distinct diseases, ALS and FTD are now considered as part of a common disease spectrum based on overlapping clinical, pathological and genetic evidence. At the cellular level, aggregation of common proteins and overlapping gene susceptibilities are shared in both ALS and FTD. Despite the convergence of these two fields of research, the underlying disease mechanisms remain elusive. However, recent discovers from ALS and FTD patient studies and models of ALS/FTD strongly suggests that synaptic dysfunction is an early event in the disease process and a unifying hallmark of these diseases. This review provides a summary of the reported anatomical and cellular changes that occur in cortical and spinal motor neurons in ALS and FTD tissues and models of disease. We also highlight studies that identify changes in the proteome and transcriptome of ALS and FTD models and provide a conceptual overview of the processes that contribute to synaptic dysfunction in these diseases. Due to space limitations and the vast number of publications in the ALS and FTD fields, many papers have not been discussed in this review. As such, this review focuses on the three most common shared mutations in ALS and FTD, the hexanucleuotide repeat expansion within intron 1 of chromosome 9 open reading frame 72 (C9ORF72), transactive response DNA binding protein 43 (TARDBP or TDP-43) and fused in sarcoma/translocated in liposarcoma (FUS), with the intention of highlighting common pathways that promote synaptic dysfunction in the ALS-FTD disease spectrum.